2019
DOI: 10.4236/ajac.2019.109026
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical Methodology for Sb(III) Traces Quantification as Emergent Contaminant in Drinks Packaged PET Samples by Solid Surface Fluorescence

Abstract: Emerging contaminants constitute a set of substances that are released into the environment for which regulations are currently not established for their environmental monitoring, being antimony one of them. A new methodology for Sb(III) traces monitoring by solid surface fluorescence is proposed. The metal was complexed with alizarine (Az) as fluorosphore reagent in alcaline medium in presence of the bile salt sodium cholate. To isolate the analyte of matrix constituents, a preconcentration/separation strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Matiazzi et al [35] reported the determination of Sb in juice flavors bottled in PET through AAS, while Uluozlu et al [36] used co-precipitation as the most adequate pre-treatment for Sn analysis in mineral water and fruit juices (detection limit 0.013 µg L −1 ). The innovative application of solid surface fluorescence (SSF) to determine Sb and Zn was proposed by Talio et al [37,38]. Authors reported limits of detection and quantification of 0.36 × 10 −3 and 1.29 × 10 −3 µg L −1 in Zn (II) and 0.08 and 0.24 µg L −1 in Sb (III), respectively.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Matiazzi et al [35] reported the determination of Sb in juice flavors bottled in PET through AAS, while Uluozlu et al [36] used co-precipitation as the most adequate pre-treatment for Sn analysis in mineral water and fruit juices (detection limit 0.013 µg L −1 ). The innovative application of solid surface fluorescence (SSF) to determine Sb and Zn was proposed by Talio et al [37,38]. Authors reported limits of detection and quantification of 0.36 × 10 −3 and 1.29 × 10 −3 µg L −1 in Zn (II) and 0.08 and 0.24 µg L −1 in Sb (III), respectively.…”
Section: Heavy Metalsmentioning
confidence: 99%